Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content 1. The Creative systems of the Arabesque and their use in silkscreen and stencil printing Mrs. Walaa Mohamed Abdelaziz 2. The features of Change in Land Usages Map at Alhanakiah City during the period from 1990-2020 using Remote Sensor Technologies Dr. Shuded Ali Alharbi, Prof. Ahmed Mohammed Alshabaan 3. The Eastern Coast of the Red Sea in Geographical Sources and the Moroccan and Andalusian Voyages between the two Centuries (4-6 AH / 10-12 AD) Using Geographic Information Systems Co-Prof. Mona Salem Al-Harbi, Co-Prof. Wafa Zabin Al-Rehily 4. The book (Almuhamashun in Islamic History) by Dr. Mahmoud Ismail in Al-Mizan Mr. Khalid Abdullah Alsaeed 5. Challenges of using modern social media on the institution of the family in The Twenty-first century – Descriptive study – Dr. Yusriya Ali Aman Al Jamil 6. The effect of governance on development quality partnerships in the Ministry of Hajj and Umrah: a prospective study in 2022 Dr. Raniah Khaled Aljohani 7. (AL)’s Process from Mythology to Language Mr. Motasim Basim Ghawadreh